Response Guided Slow Infusion of Albumin, Vasoconstrictors and Furosemide Improves Ascites Mobilization and Survival in Acute on Chronic Liver Failure: A Proof-of-Concept Study - Pande G; Hatti M; Rai MK; Rai P; Kumar K; VP K; Nehra A; Kumar S; Ranjan Rout S; Mishra SK; Kumar D; Kumar U; et al. (Dove Medical Press, 2022)
Gaurav Pande,1 Manjunath Hatti,1 Mohit Kumar Rai,2 Praveer Rai,1 Kamlesh Kumar,1 Krishna VP,1 Abhimanyu Nehra,1 Sudeep Kumar,3 Smarak Ranjan Rout,3 Sourav Kumar Mishra,3 Dinesh Kumar,4 Umesh Kumar,4 Prabhaker Mishra,5 Abdul Majeed,1 Vivek Anand Saraswat,1,* Kritika Singh,2 Harshit Singh,2 Durga Prasanna Misra,2 Vikas Agarwal2,* 1Department of Gastroenterology, Sanjay Gandhi Postgraduate Institute of Medical Sciences, Lucknow, India; 2Clinical Immunology and Rheumatology, Sanjay Gandhi Postgraduate Institute of Medical Sciences, Lucknow, India; 3Cardiology, Sanjay Gandhi Postgraduate Institute of Medical Sciences, Lucknow, India; 4Department of Advanced Spectroscopy and Imaging, Center of Biomedical Research, Lucknow, India; 5Biostatistics, Sanjay Gandhi Postgraduate Institute of Medical Sciences, Lucknow, India*These authors contributed equally to this workCorrespondence: Vikas Agarwal, Unit III, Clinical Immunology and Rheumatology, SGPGIMS, Raebareli Road, Lucknow, India, Tel +918004904390, Fax +91522268812, Email vikasagr@yahoo.comBackground and Aims: Acute-on-chronic liver failure (ACLF) with increasing organ failure is associated with poor outcomes. Severely deranged systemic hemodynamics and decreased effective arterial blood volume contribute to tissue damage and organ failure. Response-guided therapy with albumin, vasoconstrictors, and furosemide may help overcome effective hypovolemia, improve diuresis and impact survival.Methods: In the observation cohort, 230 patients with ACLF (CANONIC criteria) with ascites (≥Grade II) and ACLF ≥Grade I were enrolled. A total of 136 patients (GROUP I) received response-guided (urine sodium > 80mmol/day) slow albumin-furosemide infusion ± terlipressin (SAFI ± T), while 94 patients (GROUP II) received standard medical therapy. Twenty-eight-day survival, ascites mobilization (nil or grade 1), and adverse events were noted. In another mechanistic cohort (n = 40), laboratory evidences for improvement in various pathophysiological alterations; gut permeability, endotoxemia, cytokine storm, neutrophil dysfunction, and hemodynamic alterations following SAFI ± T/Noradrenaline (NAdr) were evaluated.Results: Age, gender, CLIF-C-ACLF, SOFA and MELD scores, ACLF grades and urine sodium were not different between the two groups in the observation cohort. Ascites was mobilized in 102/136 in GROUP I (SAFI ± T) and 23/94 in GROUP II (p < 0.05). Twenty-eight-day survival was significantly higher in GROUP I = 103/136 (75.7%) vs GROUP II = 50/94 (53.2%), (P = < 0.001). All those who were unable to reach urine sodium > 80 mmol/day died. Four patients in GROUP I developed scrotal gangrene. In the mechanistic cohort, 72% of patients survived with significant improvement in gut permeability, endotoxemia, serum cytokines, neutrophil dysfunction, and hemodynamic alterations.Conclusion: Ascitic fluid mobilization by response-guided SAFI ± T/NAdr therapy improves survival by improving splanchnic and systemic hemodynamics, decreasing gut congestion, gut permeability, and endotoxemia, improving neutrophil functions, and reducing pro-inflammatory cytokines in circulation.Graphical Abstract: Keywords: urine sodium, hemodynamics, renal artery resistive index, cytokines, neutrophil extracellular traps